2007
DOI: 10.1134/s0006297907110077
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the CD4 receptor complex proteins

Abstract: Intermolecular complexes produced by the CD4 molecule were studied. To preserve the integrity of weak protein-protein interactions of the CD4 antigen, cells were lysed in a mild nonionic detergent Brij97. Protein constituents of the complex were identified by our previously proposed fluorescence immunoprecipitation assay with subsequent mass spectrometry. In total, 26 proteins associated with CD4 were identified on CEM cells. The CD4 complex included the following major components: tyrosine phosphatase CD45, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A rather low amount of this pool can also significantly impact quantitative aspects of biochemical reactions initiating T cell activation (Chakraborty and Das, 2010). Moreover, both pY394Lck and a sizeable pool of CD45 were found in heavy DRMs suggesting that kinase activity of pY394Lck is spatially restricted and controlled by its membrane colocalization with this phosphatase (Krotov et al, 2007; Ballek et al, 2012). This observation found its support in a recent demonstration that a fraction of CD45 and CD4 are colocalized by a virtue of membrane confinement accounting for their enormously enhanced association rate (Haugh and Lauffenburger, 1997; James et al, 2011).…”
Section: Incorporating Membrane Compartmentalization Into the Model Omentioning
confidence: 99%
“…A rather low amount of this pool can also significantly impact quantitative aspects of biochemical reactions initiating T cell activation (Chakraborty and Das, 2010). Moreover, both pY394Lck and a sizeable pool of CD45 were found in heavy DRMs suggesting that kinase activity of pY394Lck is spatially restricted and controlled by its membrane colocalization with this phosphatase (Krotov et al, 2007; Ballek et al, 2012). This observation found its support in a recent demonstration that a fraction of CD45 and CD4 are colocalized by a virtue of membrane confinement accounting for their enormously enhanced association rate (Haugh and Lauffenburger, 1997; James et al, 2011).…”
Section: Incorporating Membrane Compartmentalization Into the Model Omentioning
confidence: 99%
“…9, 20 To test this possibility, we used a derivative of the Jurkat cell line deficient for Lck, J.CaM1.6 (Figure 5a). As both Jurkat and J.CaM1.6 cells demonstrated identical spot patterns in the resting and activated states (Figure 5b), we concluded that Lck was not essential for LPAP phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…It is tempting to speculate that Lck kinase, which has been reported to associate with LPAP, 9, 20 might be involved in LPAP phosphorylation. However, our data do not support this hypothesis because J.CaM1.6, a Lck-deficient Jurkat cell line, expressed identical phosphoforms of LPAP that we registered on 2D-PAGE compared with wt Jurkat cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports to date have analysed CD4 interaction complexes in lymphoid cell lines, revealing some of the well-known associating proteins, such as LCK, CD45, transferrin receptor (CD71), CD98, myosins, vimentin, tubulins, actins, annexin II and lymphocyte phosphatase associated phosphoprotein (LPAP) [29], [30], [31], [32]. However, little is known about how CD4 antigen is arranged at the surface of Mφ, which notably lack LCK expression.…”
Section: Introductionmentioning
confidence: 99%